Adult fiberoptic bronchoscope assisted tracheal intubation in a child with extremely limited mouth opening - Biswas, Binay Kumar; Choudhuri, Pratiti; Bhattarai, Balkrishna; Agarwal, Bikash (Journal of Society of Anesthesiologists of Nepal, 2015)
Tracheal intubation under vision in a child with extremely limited mouth opening requires the aid of pediatric fiberoptic bronchoscope. Often there can be only adult size bronchoscope in a center leading to a difficult situation when compromised pediatric airway requires stabilization. Aim of this case report is to describe the technique and feasibility of use of an adult fiberoptic bronchoscope for tracheal intubation of in child with extremely inadequate mouth opening unsuitable for conventional intubation. A 9-year-old boy with temporo-mandibular joint ankylosis was admitted for exploration of mastoid abscess under general anesthesia. In the absence of a pediatric fiberoptic bronchoscope we performed nasotracheal intubation of the child with the aid of an adult bronchoscope while maintaining spontaneous breathing with inhalational anesthetics. In remote locations, in centers with inadequate/nonworking equipments and in emergency situation where appropriate equipments are not available, adult fiberoptic bronchoscope may be helpful for tracheal intubation of pediatric patient. Journal of Society of Anesthesiologists of Nepal 2015; 2(2): 80-83